2008
DOI: 10.1007/s00417-008-0932-2
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of central serous chorioretinopathy following intravitreal triamcinolone injection

Abstract: Central serous chorioretinopathy exacerbation may arise as a complication of intravitreal triamcinolone acetonide injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Whether intraocular steroids induce CSCR remains to be demonstrated. The aggravation of a pre-existing CSCR and the induction of a CSCR after vitrectomy and triamcinilone injection have been described in two case reports (Imasawa et al, 2005;Kocabora et al, 2008). A systematic literature search of corticosteroid-induced CSCR reports is summarized in Table 1, indicating the incriminated drugs, routes of intake and doses.…”
Section: Corticosteroidsmentioning
confidence: 97%
“…Whether intraocular steroids induce CSCR remains to be demonstrated. The aggravation of a pre-existing CSCR and the induction of a CSCR after vitrectomy and triamcinilone injection have been described in two case reports (Imasawa et al, 2005;Kocabora et al, 2008). A systematic literature search of corticosteroid-induced CSCR reports is summarized in Table 1, indicating the incriminated drugs, routes of intake and doses.…”
Section: Corticosteroidsmentioning
confidence: 97%
“…18,82,100 Intravitreal and periocular steroid treatments are common, yet reports of CSC after local ocular steroid injections are rare; however, almost every form of exogenous glucocorticoid has been associated with exacerbation, and ocular and systemic glucocorticoids should be avoided in CSC.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Other studies indicated a statistical significant association between the development of central serous chorioretinopathy and corticosteroid medications administered not only by the oral route but also inhaled, intranasal, epidural, intra‐articular, topical dermal or periocular . Central serous chorioretinopathy development has also been described in two case reports after intraocular triamcinolone injections …”
Section: Discussionmentioning
confidence: 91%
“…18 Central serous chorioretinopathy development has also been described in two case reports after intraocular triamcinolone injections. 8,19 Available data from another populationbased study on the association between topical ophthalmic corticosteroids and central serous chorioretinopathy indicate that patients who had used topical ophthalmic corticosteroids within a year before the index date of diagnosis of central serous chorioretinopathy in the treated eye were at higher risk of developing central serous chorioretinopathy than controls. 20 No data are available regarding development of central serous chorioretinopathy in the fellow eye after topical ophthalmic administration of steroids.…”
Section: Discussionmentioning
confidence: 99%